Accelerated Organic Carbon Burial Rates Reconstructed in Elephant Butte Reservoir, New Mexico During a Megadrought - A. C. Eckland; I. Overeem; B. Carlson; K. B. Lininger (Water Resources Research)
Abstract Artificial lakes (reservoirs) accumulate sediment and organic carbon (OC) over time. We investigated sedimentation processes in a dryland reservoir and informed OC burial and potential preservation. Our study site, Elephant Butte Reservoir on the Rio Grande, New Mexico, USA receives inflows from sediment‐laden, monsoon‐driven flash floods. Using field data, historical reservoir sedimentation survey and river flux (water, sediment, and OC) data, we estimated sedimentation and carbon burial volumes and rates within the delta, reservoir bottom, and whole reservoir during wet (1980–1988) and dry (2007–2017/2019) climate periods. During severe drought (2021–2022), we measured suspended sediment and OC concentrations for characteristic (seasonal) phases of the river hydrograph, monitored delta sedimentation patterns, and observed river outflow plume dynamics. Measured suspended sediment concentrations (mean = 8,818 mg/l, median = 1,769 mg/l) frequently surpassed the hyperpycnal plume threshold (1,000 mg/l), especially during flash floods (maximum = 46,718 mg/l). River total OC content averaged 5.2% ± 12.2%, increasing to 6.3% ± 10.3% in the summer. Whole reservoir linear sedimentation averaged 3.1 ± 1.4% (dry)–4.0 ± 4.2% (wet) cm/yr, with higher rates on the reservoir bottom (5.0 ± 0.3% cm/yr) than the delta (0.8 ± 1.1% cm/yr) during drought from hyperpycnal plume deposition, potentially preserving OC. Comparisons of OC content in suspension and deposited OC in the delta indicate partial OC preservation. Estimated whole reservoir OC burial is higher during dry than wet conditions (391 ± 43.6% vs. 82.4 ± 56.4% g C/m2yr), suggesting that dryland reservoirs may be efficient carbon sinks during these periods.